Detection and Quantification of Mitochondrial Fusion Using Imaging Flow Cytometry. Issue 1 (5th July 2017) - Nascimento, Aldo; Lannigan, Joanne; Kashatus, David
Abstract: Mitochondria are dynamic organelles that perform several vital cellular functions. Requisite for these functions are mitochondrial fusion and fission. Despite the increasing importance of mitochondrial dynamics in a range of cellular processes, there exist limited methods for robust quantification of mitochondrial fission and fusion. Currently, the most widely used method to measure mitochondrial fusion is the polyethylene glycol (PEG) fusion assay. While this assay can provide useful information regarding fusion activity, the reliance on manual selection of rare fusion events is time consuming and may introduce selection bias. By utilizing the image‐capture features and colocalization analysis of imaging flow cytometry in combination with the PEG fusion assay, we are able to develop a high‐throughput method to detect and quantify mitochondrial fusion activity. © 2017 by John Wiley & Sons, Inc.